Inflammatory bowel disease, such as Ulcerative colitis, is a risk factor for recurrent thromboembolic events: a case report - O'Connor, Mortimer B (BioMed Central, 2009)
Ulcerative colitis (UC), a member of the family of inflammatory bowel disease (IBD), occurs worldwide. It has an incidence which in recent years has been rising in areas such as Southern Europe and Asia, while remaining relatively constant in Northern Europe and North America. Complications associated with UC include toxic dilatation, perforation, carcinoma and massive haemorrhage. Extra-intestinal complications also occur and these include Thromboemboli (TE). Thromboembolic disease has a greater incidence and recurrence rate among patients with IBD than the general population.